Optimizing Corporate Tax Efficiency Through Article 21 Tax Planning under Indonesia’s Tax Harmonization Law - Manrejo, Sumarno; Larasati, Ajeng Kirana (Institut Bisnis dan Informatika Kesatuan, 2025)
Tax from the company's perspective is a cost, especially since its fiscal treatment cannot be financed so efforts are needed to make efficiency. A company strategy is needed to be able to manage Income Tax, especially Article 21 because it will be imposed every month, so that efficiency efforts need to be made in order to minimize tax payments in an effort to achieve the company's expected goals. In addition, the expected positive implication is an effort to provide maximum benefits to its employees in the form of better take home pay. Unfortunately, there are still many companies that have not implemented this tax planning properly, because they assume that tax payments should be made by the recipient of the income, namely employees. However, on the one hand, employees will feel comfortable working if their tax obligations are borne or given tax allowances by their employers so that their performance is expected to be more optimal. This study was conducted with the aim of determining the implications of the application of the Income Tax Article 21 calculation method using Gross, Net and Gross-Up in an effort to carry out tax planning aimed at saving Corporate Income Tax payments at PT X in accordance with applicable tax regulations, namely the Tax Regulation Harmonization Law. The research method is descriptive quantitative. The results of the study indicate that the Income Tax Article 21 Net Method calculation method shows a better level of efficiency in paying Corporate Income Tax when compared to the Gross and Gross Up methods. Another implication is that it can provide better benefits for employees because the take home pay obtained is an amount of income received without any tax deductions for employees. The treatment of Income Tax Article 21 borne by the company can be financed by the employer so that net income will be reduced and will automatically reduce the amount of corporate tax. Keywords: Efficiency Strategy, Income Tax Article 21, Gross Method, Net Method, Gross Up Method.